Semiconductor-grade monocrystalline silicon thinning liquid and preparation method thereof
Through the semiconductor-grade single-crystal silicon thinning liquid of organic alkali system, combined with ethyl trimethylammonium iodide and dimethylethanolamine, specific components are added, which solves the cracking and surface roughness of large-diameter silicon wafers during the thinning process and the thickness of the surface of the large-diameter silicon wafers. The problem is that a more stable and uniform thinning effect is achieved, which is suitable for efficient processing of semiconductor-grade silicon wafers.
Patent Information
- Application Number
- CN202411407007.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-14
AI Technical Summary
The existing silicon wafer thinning liquid has shortcomings in terms of mechanical strength and uniformity, and it is difficult to meet the high requirements of semiconductor grades. Especially, large-diameter silicon wafers are prone to rupture during thinning and surface line marks and thickness are difficult to control.
Semiconductor grade single crystal silicon thinning liquid using organic alkali system, by combining ethyl trimethylammonium iodide with dimethylethanolamine, phthalic acid and methanesulfonic acid were added, and gloss agents and surfactants were used to prepare The thinning liquid is produced with low metal impurities, soft properties, easy to control the thinning rate, and good uniformity.
It extends the service life of the thinning liquid, reduces the color difference on the surface of the silicon wafer, improves the surface tension and permeability, reduces the roughness, improves the stability and uniformity of the thinning performance, and is suitable for high efficiency of large-diameter silicon wafers. Thinning.
Smart Images

Figure CN119307261A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thinning liquid, and in particular to a semiconductor-grade single crystal silicon thinning liquid and a preparation method thereof. Background Art
[0002] Single crystal silicon wafer is a crystal with a basically complete lattice structure. Different directions have different properties and are a good semiconductor material. The purity requirement is 99.9999%, or even above 99.9999999%. It is used for the production and deep processing of single crystal products at the diode level, rectifier device level, circuit level and solar cell level. Its subsequent products, integrated circuits and semiconductor separation devices, have been widely used in various fields and also occupy an important position in military electronic equipment.
[0003] With the development of semiconductor material technology, higher requirements are placed on the specifications and quality of silicon wafers. The market demand for large-diameter silicon wafers suitable for micro-machining will increase day by day. At present, the industry generally adopts silicon wafer thinning, silicon wafer cutting, chip mounting, chip interconnection, molding technology, deburring, cutting rib molding, soldering, coding and other processes. As the diameter of silicon wafers continues to increase, in order to increase its mechanical strength, the thickness also increases accordingly, which brings difficulties to the cutting of chips, so silicon wafers must be thinned before packaging. Larger wafers are more likely to break during the thinning process, and the larger the size, the more difficult it is to thin. The surface line marks and roughness of large-diameter silicon wafers in the chemical thinning process are related to the performance of the silicon wafers. The roughness after etching cannot be higher than 0.4μm.
[0004] At present, most of the thinning fluids on the market are hydrofluoric acid series, which have fast etching rate, but poor uniformity and high roughness, which are difficult to meet the needs of semiconductor level. Traditional inorganic alkali series thinning fluids mostly contain potassium hydroxide and sodium hydroxide, which have strong solubility, but high viscosity and many metal impurities, especially a large number of sodium ions and potassium ions are easily adsorbed on the surface during the thinning process, which are difficult to clean, have a great impact on the function of the electrical circuit, and significantly reduce the yield of the product.
[0005] Therefore, it is an urgent problem to be solved by the present invention to provide a semiconductor-grade single crystal silicon thinning liquid with low metal impurities, mild properties, easy to control thinning rate, good uniformity, low coarseness and compliance with semiconductor-grade requirements. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a semiconductor-grade single crystal silicon thinning liquid and a preparation method thereof. The semiconductor-grade single crystal silicon thinning liquid of the present invention is an organic alkali system, has low metal impurities, is milder in nature than inorganic alkalis, has easy control of thinning rate, good uniformity, low coarseness, meets semiconductor-grade requirements, and has broad market prospects.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A semiconductor-grade single crystal silicon thinning liquid comprises the following components by mass percentage:
[0009]
[0010] Preferably, the pure water is ultrapure water with a resistance of not less than 18 MΩ·cm.
[0011] Preferably, the ethyltrimethylammonium iodide has a content of ≥99% and a metal ion content of ≤1 ppb.
[0012] Purification of ethyltrimethylammonium iodide: A three-chamber two-membrane electrolyzer is used, which is designed by combining the advantages of anion exchange membrane and cation exchange membrane, that is, a reaction device that uses one anion exchange membrane and one cation exchange membrane for electrolysis at the same time, and divides the electrolyzer into three chambers, namely one anode chamber, one cathode chamber and one intermediate salt chamber. An anion exchange membrane is placed between the intermediate salt chamber and the anode chamber, and a cation exchange membrane is placed between the intermediate salt chamber and the cathode chamber. Before electrolysis, the raw material ethyltrimethylammonium iodide is placed in the intermediate salt chamber, the cathode chamber is deionized water or a low-concentration ethyltrimethylammonium iodide aqueous solution, and the anode chamber is a dielectric solution. When the two electrodes are energized, the cations in the raw materials in the intermediate chamber pass through the cation exchange membrane into the cathode chamber, and form ethyltrimethylammonium iodide with the OH- produced at the cathode, and the anions pass through the anion exchange membrane into the anode chamber, and finally obtain high-purity ethyltrimethylammonium iodide.
[0013] Preferably, the dimethylethanolamine has a content of ≥99% and a metal ion content of ≤1ppb.
[0014] Preferably, the brightener is HW306, which is a mixture of n-propanol, cyclohexylamine, sodium tetraborate, sodium saccharin and pure water in a mass ratio of 2:4:0.5:0.5:3, and the raw material grade is AR grade or higher.
[0015] More preferably, the gloss agent is prepared by the following steps: in a purified space, pure water and cyclohexylamine are added at room temperature, stirred for 20 minutes, nitrogen is introduced to control the oxygen content to less than 6%, and then the steam is turned on to raise the temperature to 70°C, saccharin sodium is slowly added, stirred for 4 hours until it is completely dissolved, the steam is turned off, the cooling water is turned on to reduce the temperature of the reactor to 40°C, sodium tetraborate is added and stirred for 3 hours, and then n-propanol is added and stirred for 30 minutes to obtain the gloss agent HW306.
[0016] Preferably, the surfactant is HW308, which is a mixture of nonylphenol polyoxyethylene ether, polyethylene glycol, glycerol, benzalkonium chloride and pure water in a mass ratio of 0.3:2:6:0.7:1, and the raw material grade is AR grade or higher.
[0017] More preferably, the surfactant is prepared by the following steps: in a purified space, pure water is added at room temperature, stirring is started at a speed of 200 rpm, benzalkonium chloride is added and stirred for 20 minutes, polyethylene glycol and glycerol are slowly added in sequence and stirred for 30 minutes, the temperature is raised to 40°C, nonylphenol polyoxyethylene ether is added, and the mixture is stirred for 1 hour at a temperature of 40°C.
[0018] Preferably, the chelating agent is one or a combination of tetrasodium ethylenediaminetetraacetate, triethanolamine, sodium hexametaphosphate, sodium ethylenediaminetetramethylenephosphate, and amine trimethylenephosphate, and the raw material content is ≥99%.
[0019] More preferably, the chelating agent is prepared by the following steps: in a purified space, at room temperature, tetrasodium ethylenediaminetetraacetate, sodium hexametaphosphate, and sodium ethylenediaminetetramethylenephosphate are mixed in a mass ratio of 1:1:2.
[0020] Preferably, the corrosion inhibitor is one or a combination of triammonium phosphate, citric acid, ammonium chloride, hexadecylamine, and hydroxyethylidene diphosphonic acid, and the raw material content is ≥99%.
[0021] More preferably, the corrosion inhibitor is prepared by the following steps: in a clean room, at room temperature, triammonium phosphate, ammonium chloride and hydroxyethylidene diphosphonic acid are mixed in a mass ratio of 0.5:1.5:3.
[0022] Another object of the present invention is to disclose a method for preparing the semiconductor-grade single crystal silicon thinning liquid, comprising the following steps:
[0023] (1) In a purified space, add half of the pure water to the reactor using a flow meter at room temperature, heat it to 45°C with steam, start stirring, rotate at 200 rpm, and slowly add ethyltrimethylammonium iodide, dimethylethanolamine, phthalic acid, methanesulfonic acid, and chelating agent in sequence, stirring until completely dissolved;
[0024] (2) After 20 minutes, raise the temperature to 60°C, add gloss agent HW306, and keep the temperature at 60°C and stir for 30 minutes;
[0025] (3) Turn off the steam, add the remaining pure water, turn on the cooling water to reduce the temperature of the reactor to 30°C, add the chelating agent and surfactant HW308 in turn and stir for 40 minutes, take samples for analysis, turn off the agitator after passing the test, start the filtration cycle, filter through 0.5μm, 0.2μm and 0.1μm filter elements for 2 hours, take samples for analysis of particle size, turn off the cycle after passing the test, and transport the reactor materials through pipelines to the packaging station in the Class 100 clean room for packaging to obtain the finished product.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention controls the decomposition of hydroxylamine during the thinning process, thereby extending the service life of the thinning liquid. The concentration of hydrogen ions has the greatest influence on the decomposition of hydroxylamine, and as hydroxylamine decomposes, the thinning effect significantly decreases. The monocrystalline silicon thinning liquid of the present invention adopts an organic base system, combines ethyltrimethylammonium iodide with dimethylethanolamine, and changes the anisotropy of silicon thinning by adding phthalic acid and methanesulfonic acid, effectively preventing the cracking of orthosilicic acid during the thinning process, and while oxidizing silicon, it can neutralize excess electrons, making the entire solution electrically neutral, preventing excess electrons from being transferred to water molecules on the silicon surface to generate OH- and H+, effectively preventing the decomposition of ethyltrimethylammonium iodide and dimethylethanolamine, and extending the service life of the thinning liquid by 50%.
[0028] The present invention solves the problem of color difference on the surface of monocrystalline silicon before and after thinning. Monocrystalline silicon wafers are prone to color difference before and after thinning, which not only affects the aesthetics of the silicon wafer, but more importantly, affects the electrical properties of the silicon wafer. Defects and color difference on the surface of the silicon wafer may form a short circuit during wafer processing, and may also cause circuit instability and conduction problems, and even degrade the performance of the silicon wafer. The present invention uses the gloss agent HW306 to solve the problem of decreased glossiness of silicon wafers after thinning.
[0029] The present invention adopts mixed surfactant HW308 to improve the surface tension of the solution, reducing it from the original 86mN / m to 62mN / m, improving the wettability to the substrate by 15% year-on-year, enhancing the permeability of the solution by 20%, making the thinning performance more uniform and stable, and reducing the roughness after thinning to 0.4μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM observation picture of a single crystal silicon wafer after being thinned by the thinning liquid of Example 1;
[0031] Figure 2 This is the SEM observation picture of the single crystal silicon wafer after thinning by the thinning liquid of comparison column 2;
[0032] Figure 3 This is a surface observation picture of a single crystal silicon wafer after being thinned by the thinning liquid of Example 1;
[0033] Figure 4 This is a surface observation picture of a single crystal silicon wafer after being thinned by the thinning liquid of Comparative Example 1;
[0034] Figure 5 This is a surface observation picture of a single crystal silicon wafer after being thinned by the thinning liquid of Comparative Example 2;
[0035] Figure 6 This is a surface observation image of a single crystal silicon wafer after thinning with the thinning liquid of Example 2. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with examples, but it should be noted that the examples do not limit the scope of protection claimed for the present invention.
[0037] A semiconductor-grade single crystal silicon thinning liquid comprises the following components by mass percentage:
[0038]
[0039] The pure water is ultrapure water with a resistance of not less than 18 MΩ·cm.
[0040] Ethyltrimethylammonium iodide, content ≥99%, metal ion ≤1ppb. Dimethylethanolamine, content ≥99%, metal ion ≤1ppb.
[0041] In the embodiment of the present invention, industrial-grade ethyl trimethyl ammonium iodide is used to purify high-purity ethyl trimethyl ammonium iodide and dimethylethanolamine with metal ions less than 1 ppb by a three-chamber two-membrane electrolytic cell method, which saves 20% of the cost compared with directly purchasing high-purity raw materials and eliminates the pollution during the transportation of raw materials. In the process of preparing the finished product, it is connected to the filling station of the 100-level clean room through a pipeline, and filtered with 0.5μm, 0.2μm and 0.1μm filter elements, and particles larger than 0.5μm are controlled to be less than 100 / ml.
[0042] Purification of ethyltrimethylammonium iodide: A three-chamber two-membrane electrolyzer is used, which is designed by combining the advantages of anion exchange membrane and cation exchange membrane, that is, a reaction device that uses one anion exchange membrane and one cation exchange membrane for electrolysis at the same time, and divides the electrolyzer into three chambers, namely one anode chamber, one cathode chamber and one intermediate salt chamber. An anion exchange membrane is placed between the intermediate salt chamber and the anode chamber, and a cation exchange membrane is placed between the intermediate salt chamber and the cathode chamber. Before electrolysis, the raw material ethyltrimethylammonium iodide is placed in the intermediate salt chamber, the cathode chamber is deionized water or a low-concentration ethyltrimethylammonium iodide aqueous solution, and the anode chamber is a dielectric solution. When the two electrodes are energized, the cations in the raw materials in the intermediate chamber pass through the cation exchange membrane into the cathode chamber, and form ethyltrimethylammonium iodide with the OH- produced at the cathode, and the anions pass through the anion exchange membrane into the anode chamber, and finally obtain high-purity ethyltrimethylammonium iodide.
[0043] The gloss agent is HW306, which is a mixture of n-propanol, cyclohexylamine, sodium tetraborate, sodium saccharin and pure water in a mass ratio of 2:4:0.5:0.5:3. The raw material grade is AR grade or higher.
[0044] In the embodiment of the present invention, the glossing agent is prepared by the following steps: in a purified space, pure water and cyclohexylamine are added at room temperature, stirred for 20 minutes, nitrogen is introduced to control the oxygen content to less than 6%, and then the steam is turned on to raise the temperature to 70°C, saccharin sodium is slowly added, stirred for 4 hours until it is completely dissolved, the steam is turned off, the cooling water is turned on to reduce the temperature of the reactor to 40°C, sodium tetraborate is added and stirred for 3 hours, and then n-propanol is added and stirred for 30 minutes to obtain the glossing agent HW306.
[0045] The surfactant is HW308, which is a mixture of nonylphenol polyoxyethylene ether, polyethylene glycol, glycerin, benzalkonium chloride, and pure water in a mass ratio of 0.3:2:6:0.7:1, and the raw material grade is AR grade or higher.
[0046] In the embodiment of the present invention, the surfactant is prepared by the following steps: in the purification space, pure water is added at room temperature, stirring is turned on, the speed is 200 rpm, benzalkonium chloride is added and stirred for 20 minutes, polyethylene glycol and glycerol are slowly added in sequence and stirred for 30 minutes, the temperature is raised to 40°C, nonylphenol polyoxyethylene ether is added, and the mixture is kept warm and stirred for 1 hour.
[0047] The chelating agent is one or a combination of tetrasodium ethylenediaminetetraacetate, triethanolamine, sodium hexametaphosphate, sodium ethylenediaminetetramethylenephosphate, and amine trimethylenephosphate, and the raw material content is ≥99%.
[0048] In the embodiment of the present invention, the chelating agent is prepared by the following steps: in a purified space, tetrasodium ethylenediaminetetraacetate, sodium hexametaphosphate, and sodium ethylenediaminetetramethylenephosphate are mixed in a mass ratio of 1:1:2 at room temperature.
[0049] The corrosion inhibitor is one or a combination of triammonium phosphate, citric acid, ammonium chloride, hexadecylamine, and hydroxyethylidene diphosphonic acid, and the raw material content is ≥99%.
[0050] In the embodiment of the present invention, the corrosion inhibitor is prepared by the following steps: in a clean room, at room temperature, triammonium phosphate, ammonium chloride and hydroxyethylidene diphosphonic acid are mixed in a mass ratio of 0.5:1.5:3.
[0051] The above-mentioned method for preparing semiconductor-grade single crystal silicon thinning liquid comprises the following steps: in a clean space, add half of the pure water to the reactor at room temperature using a flow meter, heat it to 45°C with steam, start stirring, rotate at 200 rpm, slowly add ethyltrimethylammonium iodide, dimethylethanolamine, phthalic acid, methanesulfonic acid, and chelating agent in turn, stir until completely dissolved, raise the temperature to 60°C after about 20 minutes, add gloss agent HW306, keep warm at 60°C and stir for 30 minutes. Turn off the steam, add the remaining pure water, turn on the cooling water to reduce the temperature of the reactor to 30°C, add chelating agent and surfactant HW308 in turn and stir for 40 minutes, take samples to analyze the content, density, PH and other indicators, turn off the stirrer after passing the test, start filtering circulation, filter through 0.5μm, 0.2μm and 0.1μm filter elements for 2 hours, take samples to analyze the particle size, turn off the circulation after passing the test, and transport the reactor materials through a pipeline to the packaging station of the Class 100 clean room for packaging to obtain the finished product.
[0052] In order to illustrate the performance advantages of the semiconductor-grade single crystal silicon thinning liquid of the present invention, the following is described by comparing Examples 1-5 with Comparative Examples 1-5:
[0053] Example 1
[0054] The semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 20% ethyltrimethylammonium iodide, 8% dimethylethanolamine, 5% phthalic acid, 4% methanesulfonic acid, 2% brightener HW306, 0.5% chelating agent, 0.2% corrosion inhibitor, 0.1% surfactant HW308, and 60.2% pure water.
[0055] Example 2
[0056] The semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 25% ethyltrimethylammonium iodide, 12% dimethylethanolamine, 1% phthalic acid, 2% methanesulfonic acid, 5% brightener HW306, 1.0% chelating agent, 0.8% corrosion inhibitor, 0.6% surfactant HW308, and 52.6% pure water.
[0057] Example 3
[0058] The semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 22% ethyltrimethylammonium iodide, 10% dimethylethanolamine, 2% phthalic acid, 1% methanesulfonic acid, 3% brightener HW306, 0.7% chelating agent, 0.7% corrosion inhibitor, 0.5% surfactant HW308, and 60.1% pure water.
[0059] Example 4
[0060] The semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 21.5% ethyltrimethylammonium iodide, 9.5% dimethylethanolamine, 3% phthalic acid, 2% methanesulfonic acid, 2.5% brightener HW306, 0.55% chelating agent, 0.4% corrosion inhibitor, 0.25% surfactant HW308, and 60.3% pure water.
[0061] Example 5
[0062] The semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 23% ethyltrimethylammonium iodide, 11% dimethylethanolamine, 3% phthalic acid, 1% methanesulfonic acid, 3.5% brightener HW306, 0.6% chelating agent, 0.55% corrosion inhibitor, 0.45% surfactant HW308, and 56.9% pure water.
[0063] Comparative Example 1
[0064] The semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 20% ethyltrimethylammonium iodide, 8% dimethylethanolamine, 5% phthalic acid, 4% methanesulfonic acid, 0.5% chelating agent, 0.2% corrosion inhibitor, 0.1% surfactant HW308, and 62.2% pure water.
[0065] Comparative Example 2
[0066] The semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 25% ethyltrimethylammonium iodide, 12% dimethylethanolamine, 1% phthalic acid, 2% methanesulfonic acid, 1.5% brightener HW306, 1.0% chelating agent, 0.8% corrosion inhibitor, 0.60% surfactant HW308, and 56.1% pure water.
[0067] Comparative Example 3
[0068] Semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 22% ethyltrimethylammonium iodide, 10% dimethylethanolamine, 2% phthalic acid, 1% methanesulfonic acid, 3% brightener HW306, 0.7% chelating agent, 0.7% corrosion inhibitor, 0.05% surfactant HW308, 60.55% pure water
[0069] Comparison column 4
[0070] The semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 20% ethyltrimethylammonium iodide, 8% dimethylethanolamine, 2% brightener HW306, 0.5% chelating agent, 0.2% corrosion inhibitor, 0.1% surfactant HW308, and 69.2% pure water.
[0071] Comparative Example 5
[0072] The semiconductor single crystal silicon thinning liquid is prepared according to the following components in mass percentage: 20% ethyltrimethylammonium iodide, 8% dimethylethanolamine, 5% phthalic acid, 4% methanesulfonic acid, 2% brightener HW306, 0.5% chelating agent, 0.2% corrosion inhibitor, and 60.3% pure water.
[0073] Thinning process: Prepare the thinning liquid of corresponding concentration according to the formula requirements, soak it for 150 seconds at 40℃ and 400 rpm, take out the silicon wafer and immediately rinse it with pure water, blow it dry with nitrogen, then observe the plan view of the silicon wafer with a scanning electron microscope, and test the roughness after thinning with a surface roughness tester.
[0074] Single crystal silicon wafer, 40℃, thinning for 150 seconds, the experimental test results are as follows:
[0075]
[0076] Examples 1 to 5 all meet the process requirements.
[0077] Figure 1 This is a SEM observation picture of a single crystal silicon wafer after thinning with the thinning liquid of Example 1. The surface is uniform and has no pores.
[0078] Figure 2 For comparison, the SEM observation of the single crystal silicon wafer after thinning with the thinning liquid in column 2 shows that the surface is uneven and very rough.
[0079] Comparison Example 1 and Example 1 show that the color difference of the matte agent HW306 in Comparison Example 1 before and after thinning is very obvious under the same conditions (see Figure 3 and Figure 4 ).
[0080] Figure 5 This is a surface observation picture of a single crystal silicon wafer after being thinned by the thinning liquid of Comparative Example 2;
[0081] Figure 6 This is a surface observation picture of a single crystal silicon wafer after thinning with the thinning liquid of Example 2. There is no color difference, the surface is uniform, and there are no holes.
[0082] Compared with Example 2, the content of gloss agent HW306 in Comparative Example 2 is lower, and there is a slight color difference before and after thinning under the same conditions, such as Figure 5 and Figure 6 shown.
[0083] Comparative Example 3 Compared with Example 3, the amount of surfactant HW308 added in Comparative Example 3 is lower, and the roughness after thinning is 0.46μm, which is slightly higher than the required 0.4μm.
[0084] Compared with Example 1, in Comparative Column 4, no phthalic acid and methanesulfonic acid were added, resulting in the decomposition of ethyltrimethylammonium iodide and dimethylethanolamine, and the service life was reduced by 50%.
[0085] Compared with Example 1, in Comparative Example 5, surfactant HW308 was not added, and the roughness after thinning increased to 0.89 μm, which did not meet the requirements.
[0086] The technical solutions provided by the embodiments of the present invention are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the embodiments of the present invention. The description of the above embodiments is only applicable to help understand the principles of the embodiments of the present invention. At the same time, for those skilled in the art, according to the embodiments of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A semiconductor-grade single crystal silicon thinning liquid, characterized in that: The composition includes the following components by mass percentage:
2. The semiconductor-grade single crystal silicon thinning liquid according to claim 1, characterized in that: The pure water is ultrapure water with a resistance of not less than 18 MΩ·cm; the ethyltrimethylammonium iodide has a content of ≥99% and metal ions of ≤1 ppb; the dimethylethanolamine has a content of ≥99% and metal ions of ≤1 ppb.
3. The semiconductor-grade single crystal silicon thinning liquid according to claim 1, characterized in that: The gloss agent is HW306, which is a mixture of n-propanol, cyclohexylamine, sodium tetraborate, sodium saccharin and pure water in a mass ratio of 2:4:0.5:0.5:3, and the raw material grade is AR grade or higher.
4. The semiconductor-grade single crystal silicon thinning liquid according to claim 3, characterized in that: The glossing agent is prepared by the following steps: adding pure water and cyclohexylamine at room temperature in a purified space, stirring for 20 minutes, introducing nitrogen to control the oxygen content to be less than 6%, then turning on the steam to raise the temperature to 70°C, slowly adding saccharin sodium, stirring for 4 hours until it is completely dissolved, turning off the steam, turning on the cooling water to lower the temperature of the reactor to 40°C, adding sodium tetraborate and stirring for 3 hours, and then adding n-propanol and stirring for 30 minutes to obtain the glossing agent HW306.
5. The semiconductor-grade single crystal silicon thinning liquid according to claim 1, characterized in that: The surfactant is HW308, which is a mixture of nonylphenol polyoxyethylene ether, polyethylene glycol, glycerol, benzalkonium chloride and pure water in a mass ratio of 0.3:2:6:0.7:1, and the raw material grade is AR grade or higher.
6. The semiconductor-grade single crystal silicon thinning liquid according to claim 5, characterized in that: The surfactant is prepared by the following steps: in a purified space, pure water is added at room temperature, stirring is started at a speed of 200 rpm, benzalkonium chloride is added and stirred for 20 minutes, polyethylene glycol and glycerol are slowly added in sequence and stirred for 30 minutes, the temperature is raised to 40° C., nonylphenol polyoxyethylene ether is added, and the mixture is stirred for 1 hour at a temperature of 40° C.
7. The semiconductor-grade single crystal silicon thinning liquid according to claim 1, characterized in that: The chelating agent is one or a combination of tetrasodium ethylenediaminetetraacetate, triethanolamine, sodium hexametaphosphate, sodium ethylenediaminetetramethylenephosphate, and amine trimethylenephosphate, and the raw material content is ≥99%; the corrosion inhibitor is one or a combination of triammonium phosphate, citric acid, ammonium chloride, hexadecylamine, and hydroxyethylidene diphosphonic acid, and the raw material content is ≥99%.
8. The semiconductor-grade single crystal silicon thinning liquid according to claim 7, characterized in that: The chelating agent is prepared by the following steps: in a purified space, under room temperature conditions, tetrasodium ethylenediaminetetraacetate, sodium hexametaphosphate, and sodium ethylenediaminetetramethylenephosphate are mixed in a mass ratio of 1:1:
2.
9. The semiconductor-grade single crystal silicon thinning liquid according to claim 7, characterized in that: The corrosion inhibitor is prepared by the following steps: in a purified space, at room temperature, triammonium phosphate, ammonium chloride and hydroxyethylidene diphosphonic acid are mixed in a mass ratio of 0.5:1.5:
3.
10. A method for preparing a semiconductor-grade single crystal silicon thinning liquid according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) In a purified space, add half of the pure water to the reactor using a flow meter at room temperature, heat it to 45°C with steam, start stirring, rotate at 200 rpm, and slowly add ethyltrimethylammonium iodide, dimethylethanolamine, phthalic acid, methanesulfonic acid, and chelating agent in sequence, stirring until completely dissolved; (2) After 20 minutes, raise the temperature to 60°C, add gloss agent HW306, and keep the temperature at 60°C and stir for 30 minutes; (3) Turn off the steam, add the remaining pure water, turn on the cooling water to reduce the temperature of the reactor to 30°C, add the chelating agent and surfactant HW308 in turn and stir for 40 minutes, take samples for analysis, turn off the agitator after passing the test, start the filtration cycle, filter through 0.5μm, 0.2μm and 0.1μm filter elements for 2 hours, take samples for analysis of particle size, turn off the cycle after passing the test, and transport the reactor materials through pipelines to the packaging station in the Class 100 clean room for packaging to obtain the finished product.